2019
DOI: 10.1039/c8tb02195c
|View full text |Cite
|
Sign up to set email alerts
|

High modulus, enzyme-degradable poly(trimethylene carbonate)–peptide biohybrid networks formed from triblock prepolymers

Abstract: Biohybrid networks have the potential to have stiffnesses equivalent to that of native soft connective tissues as well as cell-mediated degradation behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…[24,[26][27][28][29]31,33] There are many examples of degradable cross-links incorporated within networks, the degradation of which are controlled by various applied stimuli. [33][34][35][36][37][38][39] In addition to the development of labile networks by engineering degradable crosslinks, some networks are degraded by bond cleavage within the backbone itself, rather than degradation of the individual cross-links. [34,[40][41][42][43] Herein, the copolymerization of phthalaldehyde with asymmetric allyl phthalaldehyde is explored followed by crosslinking via a thiol-ene photopolymerization with a multifunctional thiol and then the degradation of the cross-linked networks via triggered self-immolation (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%
“…[24,[26][27][28][29]31,33] There are many examples of degradable cross-links incorporated within networks, the degradation of which are controlled by various applied stimuli. [33][34][35][36][37][38][39] In addition to the development of labile networks by engineering degradable crosslinks, some networks are degraded by bond cleavage within the backbone itself, rather than degradation of the individual cross-links. [34,[40][41][42][43] Herein, the copolymerization of phthalaldehyde with asymmetric allyl phthalaldehyde is explored followed by crosslinking via a thiol-ene photopolymerization with a multifunctional thiol and then the degradation of the cross-linked networks via triggered self-immolation (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Prepolymer and initial network characterization A target average PTMC block length of 8 repeating TMC units was chosen for each prepolymer, to provide a prepolymer with appreciable water solubility to facilitate degradation [17]. This PTMC block length was achieved for the VS-PTMC-MA, while an average block length of 9 TMC units was obtained for the VS-PTMC-PEG-MA.…”
Section: Resultsmentioning
confidence: 99%
“…Heterobifunctional PTMC and PEG-PTMC were synthesised, fractionated, and characterized as described previously [17]. Briefly, PTMC was synthesized by ring-opening melt polymerization of TMC using 2-((2-vinylsulfonyl ethyl)thio)ethanol as initiator and stannous 2-ethylhexanoate as catalyst, and then methacrylated by reaction of methacryloyl chloride with the terminal hydroxyl group.…”
Section: Network Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The use of MMP-specific peptide sequences to control spatial and temporal degradation [14][15][16][17] is most commonly used in hydrogels due to the water-swollen network increasing accessibility of the peptide sequence to water-soluble enzymes. [18][19][20][21] Recent studies have demonstrated incorporation of bioactive peptide into nylons, 22 however, the use of enzyme-sensitive peptides to control resorption of high molecular weight thermoplastics remains unreported. Zorn and colleagues polymerized oligopeptide segments into polyurethanes 23 for the purpose of improving polymer biodegradation.…”
Section: Introductionmentioning
confidence: 99%